2021
DOI: 10.1161/jaha.121.022224
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Blood Pressure Control Performance and Process Metrics in 25 US Health Systems: The PCORnet Blood Pressure Control Laboratory

Abstract: Background The National Patient‐Centered Clinical Research Network Blood Pressure Control Laboratory Surveillance System was established to identify opportunities for blood pressure (BP) control improvement and to provide a mechanism for tracking improvement longitudinally. Methods and Results We conducted a serial cross‐sectional study with queries against standardized electronic health record data in the National Patient‐Centered Clinical Research Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
17
2
Order By: Relevance
“…The BP Control Lab is an established research collaboration, including 27 health systems, that leverages PCORnet infrastructure, including the PCORnet common data model (CDM), to support large-scale observational studies and national surveillance, large pragmatic RCTs, and local quality improvement efforts centered on hypertension and related cardiovascular disease [13] , [14] . The PCORnet CDM facilitates standardization of EHR data, including patient demographics, encounters, diagnoses, procedures, medications (prescribed and dispensed), vitals, laboratory measures, and related domains.…”
Section: Methodsmentioning
confidence: 99%
“…The BP Control Lab is an established research collaboration, including 27 health systems, that leverages PCORnet infrastructure, including the PCORnet common data model (CDM), to support large-scale observational studies and national surveillance, large pragmatic RCTs, and local quality improvement efforts centered on hypertension and related cardiovascular disease [13] , [14] . The PCORnet CDM facilitates standardization of EHR data, including patient demographics, encounters, diagnoses, procedures, medications (prescribed and dispensed), vitals, laboratory measures, and related domains.…”
Section: Methodsmentioning
confidence: 99%
“…In an analysis of real-world data from 1.7 million patients with hypertension a blood pressure goal of < 130/80 mmHg and < 140/90 mmHg was achieved in 30% and 62% of patients, respectively. Control of BP varied across race and ethnicity with Black patients having the lowest blood pressure control [5] . Our study showed that during the pandemic patients were less likely to have their blood pressure monitored and less likely to achieve their guideline-directed blood pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no studies have explored BP seasonal variation in adults with hypertension across the US nor investigated seasonal fluctuation in BP control metrics, such as BP control or antihypertension medication intensification. Therefore, we aimed to estimate the magnitude of the seasonal variation in population-based BP control measures in the US, and the extent to which outdoor temperature and precipitation explains this variation using data from the PCORnet BP Control Laboratory Surveillance System (BP Track) [18,19].…”
Section: Introductionmentioning
confidence: 99%